The Synergy between PPATK and Investigators in In Rem Asset Forfeiture within Civil Forfeiture Procedures : Sinergitas PPATK dan Penyidik pada Perampasan Aset Secara In Rem dalam Prosedur Civil Forfeiture - Djalil, Mochammad; Mufidah, Nuruz Zakiyatul; Habibi, Miftakhur Rokhman (Al-Jinayah : Jurnal Hukum Pidana Islam, 2025)
Asset confiscation arising from criminal acts, particularly corruption, is a vital instrument for preventing offenders from enjoying illicit gains and for restoring state financial losses. However, Indonesia’s asset recovery rate remains low due to regulatory challenges, weak interagency coordination, and limited Non-Conviction-Based Asset Forfeiture (NCB) mechanisms. Therefore, new legal formulations are required to address these obstacles. This study employs legal research methods, including statutory, conceptual, and case approaches. The findings indicate that the in rem approach, which targets assets without requiring criminal conviction, is more efficient and adaptive in combating corruption, aligning with UNCAC 2003 recommendations. Effective synergy between the Financial Transaction Reports and Analysis Center (PPATK) and investigators is crucial for asset tracing, freezing, and confiscation, despite ongoing issues with data access and regulatory harmonization. Legal reform, strengthened international cooperation, and the protection of human rights are essential to optimize asset confiscation for justice and state financial recovery.